“Workplace stress and job satisfaction among the teaching faculty of selected nursing institutions at Sangli district” (Journal of Pharmaceutical Negative Results, 2022)
A study was carried out to assess the workplace stress and job satisfaction among the teaching faculty of selected nursing institutes at Sangli district. Research objectives were to assess workplace stress among teaching faculty, to assess the job satisfaction among teaching faculty and to find the co-relation between work place stress and job satisfaction. Assumptions of the study were teaching faculty may have some work place stress, teaching faculty may have some job satisfaction and work place stress might be related to job satisfaction. The conceptual framework for the study was based on the Irvin Rosenstock’s Health Belief Model. The research design used was quantitative cross sectional descriptive research design. Sample size consist of 100 teaching faculty selected by using non- probability convenient sampling technique. Self-structured work place stress scale was used for the collection of data related to workplace stress among teaching faculty of nursing institutes and modified generic job satisfaction scale1 to assess the job satisfaction. The data was analyzed using descriptive and inferential statistics. The findings of the study revealed that 45% of nursing teachers had low level of workplace stress, 35% of them had moderate level of workplace stress and 20% of them had high level of workplace stress. While considering job satisfaction, 59% had high job satisfaction. Thus the ‘r’ value is -0.69, and hence work place stress and job satisfaction are negatively related to each other, which means when one increases, other decreases. Thus it can concluded that when work place stress increases job satisfaction decreases.